(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
Essentially, hospitality is the reception of visitors, guests, or strangers. More specifically, it refers to the provision of hosting services and describes a positive relationship between the host, who is acting with goodwill, and the guest, who is most commonly seeking food, shelter, safety, and/or entertainment. To create a comprehensive hospitality definition, it is first important to explore what hospitality means as a concept. The word ‘hospitality’ itself has emerged from the Latin word ‘hospes’, which means ‘visitor’, ‘guest’, or ‘stranger’, and this is a good starting point when creating a working hospitality definition. Hospitality is about extending a welcome to a visitor and providing them with some form of comfort. A good way to think of the objective of hospitality is to view it as the provision of a ‘home away from home’ for people to enjoy. [Adler, N. J. and Graham, J. L. (1989).]